AGENSIFIKASI (AGENCIFICATION) DAN EFIENSI: ANALANALISIS PADA BADAN LAYANAN UMUM RUMAH SAKIT - Aditia, -; Waluyo, Budi (Polytechnic of State Finance STAN, 2015)
Agencification is a kind of public service reform aimed to achieving good governance.Â Agencification on several public agencies in Indonesia is conducted through the implementation of Financial Management Pattern on Public Service Agency. This model emphasizes the application of financial flexibility, the principles of productivity, effiency, and effectiveness. In health sector, the government has required the implementation of Financial Management Pattern Public Service Agency for government hospitals.The purpose of this study is to measure the efficiency of the selected Hospitals, which implement Public Service Agency, based on the hospital classification and identify input variavbles that significantly affect the efficiency of the Hospitals. This study describes a through and deep understanding around the calculation and analysis of the efficiency of the central Hospitals. This study uses a quantitative approuch to obtain evidence related to the measurement of Hospitals efficiency. Data and information obtained through observation and study of documentation. Furthermore, the data were statistically analyzed using Data Envelopment Analysis models.The analysis showed that for General Hospital, 9 of 17 instituctions are efficient in relative and 8 institutions are inefficient relative to the other. Meanwhile, for Special Hospital, 10 of 17 institutions are efficient in relative and 7 instutions are infficient relative to the other. Input variables that significantly influence the efficiency of the Hospitals are considered the number of beds (with coefficient 114.6217), the number of doctors (with coefficient -55.52), and the number of health workers other than doctors (with coefficient -1.849583). While the other two input variables, namely the number of non-health personnel and operating expenses do not significantly affect the efficiency of the Hospitals.